2014
DOI: 10.4238/2014.august.25.4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and clinical significance of lymph node metastases near the recurrent laryngeal nerve from thoracic esophageal carcinoma

Abstract: ABSTRACT. This study aimed to evaluate the characteristics of lymph node (LN) metastases from thoracic esophageal carcinoma near the recurrent laryngeal nerve and the influence of these metastases on patient prognosis and to determine the reasonable regional LN dissection range. The clinical data from 120 patients who underwent resection for thoracic esophageal carcinoma were analyzed retrospectively. LN metastases near the recurrent laryngeal nerve were detected in 34.2% of the cases, and the metastasis rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 9 publications
5
30
0
Order By: Relevance
“…Furthermore, Yoshioka et al (44) reported the rate of cervical lymph node metastasis was 51.6% in patients with lymph node metastasis near the recurrent laryngeal nerve, while the rate was 11.6% in patients without lymph node metastasis near the recurrent laryngeal nerve (P<0.05). At the same time, Ye et al (43) reported the significant higher rate of 3-year survival in patients with lymph node metastasis near the recurrent laryngeal nerve after radical surgery with 3-FL than patients without recurrent laryngeal nerve lymph node metastasis (29.3% vs. 58.2%, respectively P<0.05). Malassagne et al (45) showed the similar outcomes with the lower rate of 5-year survival in patients with metastatic recurrent laryngeal nerve lymph node after 3-FL than that of patients with non-LN metastasis (21% vs. 47%, respectively, P<0.05).…”
Section: The Impact Of Recurrent Laryngeal Nerve Lymph Node Metastasismentioning
confidence: 91%
See 4 more Smart Citations
“…Furthermore, Yoshioka et al (44) reported the rate of cervical lymph node metastasis was 51.6% in patients with lymph node metastasis near the recurrent laryngeal nerve, while the rate was 11.6% in patients without lymph node metastasis near the recurrent laryngeal nerve (P<0.05). At the same time, Ye et al (43) reported the significant higher rate of 3-year survival in patients with lymph node metastasis near the recurrent laryngeal nerve after radical surgery with 3-FL than patients without recurrent laryngeal nerve lymph node metastasis (29.3% vs. 58.2%, respectively P<0.05). Malassagne et al (45) showed the similar outcomes with the lower rate of 5-year survival in patients with metastatic recurrent laryngeal nerve lymph node after 3-FL than that of patients with non-LN metastasis (21% vs. 47%, respectively, P<0.05).…”
Section: The Impact Of Recurrent Laryngeal Nerve Lymph Node Metastasismentioning
confidence: 91%
“…It's believed that the dissection of the recurrent laryngeal nerve lymph node would bring a better OS after operation than those without the recurrent laryngeal nerve lymph node dissection. And the patient with positive recurrent laryngeal nerve lymph nodes who has undergone the radical esophagectomy with 3-FL will get more benefits of postoperative survival rate than patients with 2-FL (43)(44)(45). At the same time Kato et al (63) have once reported that the rate of local recurrence in 3-FL group was lower than that in Ivor-Lewis group (17% versus 38%) regardless of whether there's cervical or upper mediastinal lymph node metastasis or not.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations